Synthesis and Antimicrobial Screening of Quinazolone Containing Novel Heterocyclic Schiff Base and Azetidinone by Niementowski Reaction. Issue 2 (2005) - Desai, A. R.; Roy, R. U.; Desai, K. R.
Abstract : Several 2-[2-{(4-substitutedbenzylidene)-phenyl}vinyl]-4-oxo-3, 4-dihydroquinazolone-6-sulfonicacid 4(a-l) and 2-[2-{4-(3-chloro-4-substituedphenyl-azetidin-2-one)-phenyl}vinyl]-4-oxo-3, 4-dihydroqui-nazolone-6-sulfonic acid 5(a-l) were synthesized by using conventional techniques and were screened for antibacterial and antifungal activity. The compounds showed good to moderate antimicrobial activity and were characterized on the basis of spectral analysis.